P455 Spacing of infliximab infusions over 8 weeks in patients with inflammatory bowel diseases in clinical remission: Final results of a retrospective multicentre French national cohort. (16th January 2018) - Dufour, G; Pariente, B; Amiot, A; Viennot, S; Zerbib, F; Caillo, L; Nancey, S; Pouderoux, P; Poullenot, F; Altwegg, R; Peyrin-Biroulet, L; Nachury, M; et al.
Abstract: Background: Numerous patients with inflammatory bowel diseases (IBD) are currently treated with infliximab (IFX) infusions every 8 weeks as maintenance therapy. To date there is no clear guidelines on IFX treatment de-escalation. The aim of our study was to evaluate the effect of a spacing of IFX infusions over 8 weeks on clinical remission in IBD patients. Methods: This was a retrospective multicentre French national cohort including all IBD patients treated with IFX who were in clinical remission according to the referring physician and had a spacing of their infusion interval over 9 weeks for at least two consecutive infusions. Failure of IFX spacing was defined as a clinical relapse (which leads to IFX optimisation) and/or an IFX withdrawal for failure or intolerance and/or a prescription of an immunosuppressive drug and/or an intestinal resection for IBD. Results: One hundred and fifty-one patients (61F, 90M) were included (100 Crohn's disease [CD] and 51 ulcerative colitis [UC]) with a median follow-up after spacing of 36.9 (IQR: 15.1–56.7) months. Median duration of IFX before spacing was 39.1 (17.4–67.8) months. Forty-eight (32%) patients had an immunosuppressive drug with IFX at spacing. Maximum infusion interval was 13 weeks and 49 (32%) patients had an infusion interval ≥ at 12 weeks. Globally, 49 (32%) patients had a failure of IFX spacing during follow-up. Cumulative probability of failure free survival was 88.3% ± 2.7% at 1 year and 75.6% ± 3.7% at 2 years. Patients with a failure of IFX spacing had an IFX optimisation with clinical response in 38 (78%) patients. In the all cohort, five (3%) patients had a withdrawal of IFX for infusion reaction or immunisation and six (4%) for secondary loss of response. The median duration of IFX before spacing was significantly shorter in patients with failure of IFX spacing compared with patients without failure (22.9 months [15.8–48] vs. 45.1 months [23.5–76.6], respectively, p < 0.001). IFX treatment duration before spacing >4 years was significantly associated to a decreased risk of IFX spacing failure (log-rank, p = 0.048). Regarding CD, the colonic location (HR = 0.5; IC 95% 0.3–0.7; p = 0.01) and the duration of IFX before spacing (HR = 0.98; IC 95% 0.96–0.99; p = 0.007) were significantly associated to a decreased risk of IFX spacing failure. For UC, the only factor associated to the risk of IFX spacing failure was the extension of the disease (log-rank, p = 0.023). Conclusions: More than three-quarter of the IBD patients who had a spacing of their IFX infusions over 8 weeks remained in clinical remission 2 year after spacing. The main clinical factor associated to success of IFX spacing was a prolonged IFX treatment duration before spacing.